The Influence of Work Discipline and Motivation on Performance Employees in Regional Government Organizations - Rahmani, Yulia; Meinar R, Anistya; TW, Titik Esthi; Nurhadi, Suprih; Qomariah, Nurul (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2024)
Every organization, whether government-owned or private-owned, is obliged to provide the best service to service users by improving the performance of its employees. This research was planned to have the aim of knowing and analyzing work discipline and work motivation of employees in government organizations. The independent variables used are work discipline and work motivation variables, while the dependent variable is employee performance. The planned method that will be used is descriptive analysis, validity and reliability testing and hypothesis testing. The results of this research produce two hypotheses, namely the first hypothesis, namely that work discipline is expected to improve performance. The second hypothesis is that work motivation is expected to improve employee performance.